Avaliação visceral da técnica sorológica para Leishmaniose visceral e doença de Chagas em animais silvestres e identificação molecular - Tenório, Michely da Silva [UNESP] (2015)
Wild animals are important sources of infection of leishmaniasis and Chagas disease to domestic animals and humans. The employment of PCR with ITS1 primers plus cloning and sequencing target DNA allows to characterize parasitic species. By using specific immunoreagents also enable investigation of natural infection between different species of wild animals for both diseases. Flagellate isolates in LIT medium (blood culture) were assessed of 103 animals coming from the Wildlife Conservation Center of Ilha Solteira -SP and 118 serum samples. In immunoassays, recombinant proteins CRA and FRA fromTrypanosoma cruzi and rK39 from Leishmania infantum were used. Species -specific conjugates were produced for different animal species and used in indirect ELISA and the protein A conjugate was evaluated for serological tests with use of rK39. Sera from dogs reagents for visceral leishmaniasis and for humans reagents for Chagas disease were tested for reactivity against these proteins. Flagellate protozoa were observed in LIT culture medium, at the following free-living species: common agouti (D. agouti), white-eared opossum (D. albiventris) and nine-banded armadillo (D. novemcinctus); and from a captive black howler monkey (A. caraya). Products were amplified by PCR (585bp) from blood culture in wild animals and from an animal in captivity (650bp) in whole blood sample. The amplified products were inserted into cloning vector and sequenced resulting in 97% similarity with T. cruzi to white-eared opossum an common agouti (acess number: AF 362825.1) and 98% to nine-banded armadillo (acess number: GQ 258720.1). The isolated from black howler monkey was 90% similar to T. minasense (acess number: AB 362411.1). The results present the first report of these parasitic species of epidemiological importance in the studied area and demonstrated advantage in the association of blood culture to molecular techniques to characterize flagellates. For ...